2017
DOI: 10.1038/s41598-017-15685-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and evaluation of two different methods to establish the cigarette smoke exposure mouse model of COPD

Abstract: Animal model of cigarette smoke (CS) –induced chronic obstructive pulmonary disease (COPD) is the primary testing methodology for drug therapies and studies on pathogenic mechanisms of disease. However, researchers have rarely run simultaneous or side-by-side tests of whole-body and nose-only CS exposure in building their mouse models of COPD. We compared and evaluated these two different methods of CS exposure, plus airway Lipopolysaccharides (LPS) inhalation, in building our COPD mouse model. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 24 publications
6
51
2
Order By: Relevance
“…These changes were not induced by ECVs lacking nicotine, thus supporting the direct harmful effects of nicotine. All these inflammatory mediators and enzymes were similarly found to be stimulated in other experiments treating mice with CS …”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 54%
See 2 more Smart Citations
“…These changes were not induced by ECVs lacking nicotine, thus supporting the direct harmful effects of nicotine. All these inflammatory mediators and enzymes were similarly found to be stimulated in other experiments treating mice with CS …”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 54%
“…These data demonstrate that acute exposure to e‐cigarette aerosol in mouse lung induces inflammatory responses. Chronic exposure of mice to nicotine‐containing ECV over a 4‐month period induced respiratory resistance and alveolar airspace enlargement reminiscent of features of COPD, as also found in CS‐exposed mice . Moreover, the nicotine‐containing ECV induced increased levels of IL‐1β and MCP‐1 in the lungs, as well as protease, collagenase and cathepsin expression, all of which are involved in the pathogenesis of COPD.…”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 69%
See 1 more Smart Citation
“…Emerging evidence suggests that infection and persistent inflammation are key players in the pathogenesis of COPD. Furthermore, our earlier study demonstrated that the combination of LPS and CS causes significant changes in airway inflammation and lung function (Shu et al, 2017). Studies have also reported that the combination of CS and LPS can shorten the period of development of an experimental COPD model (Mizutani et al, 2009;Zhou, Tan, Kuang, Liu, & Wan, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…As previously described (Shu et al, 2017), the mean linear intercept was determined by counting the diameter of air spaces in 10 random fields per slide to assess alveolar enlargement and destruction. As previously described (Shu et al, 2017), the mean linear intercept was determined by counting the diameter of air spaces in 10 random fields per slide to assess alveolar enlargement and destruction.…”
Section: Histological Staining and Morphological Analysismentioning
confidence: 99%